Some merry adventures of Robin Hood of great renown in Nottinghamshire - Pyle, Howard 1853-1911. (New York Scribner, 1954)
Twelve selected adventures of Robin Hood and his outlaw band who stole from the rich to give to the poor.
Keywords: Robin Hood (Legendary character) -- Legends; Robin Hood (Legendary character) -- Legends